An In-depth Analysis of the Mechanical, Electrical, and Drug Release Properties of Gelatin–Starch Phase-Separated Hydrogels. (1st November 2016) - Mallick, S. P.; Shaw, G. S.; Uvanesh, K.; Biswal, D.; Nayak, Suraj; Sagiri, S. S.; Singh, V. K.; Bhattacharya, M. K.; Anis, A.; Pal, K.
ABSTRACT: Gelatin–starch-based phase-separated hydrogels were prepared in this study. Corn starch, soluble starch, and hydrated starch were used as the representative starches for the preparation of the hydrogels. Bright field microscopy suggested the formation of phase-separated hydrogels. An increase in the hydrophilic nature of the starch molecules resulted in decrease in the agglomeration of the starch particles within the gelatin matrices. Fourier transform infrared study confirmed the presence of starch particles within the hydrogels. X-ray diffraction studies suggested that the higher degree of crystallinity of corn starch and soluble starch was responsible for the comparative hydrophobic nature of these starch particles. Hydrated starch was found to be amorphous in nature and can be explained by the destruction of the intramolecular associative forces. Stress relaxation and creep recovery studies indicated predominant elastic nature of the hydrogels. Hydrated starch-containing hydrogels were firmer than corn starch and soluble starch because of the better miscibility of the hydrated starch particles within the gelatin matrices. The bulk resistance of the starch-containing hydrogels was higher. This was because of the capability of the starch particles to behave as dielectric medium. Incorporation of starch particles within the gelatin matrix was found to increase the polymer relaxation-mediated drug diffusion. Metronidazole-loaded hydrogels were found to have good antimicrobial activity. GRAPHICAL ABSTRACT: